Associated factors to an unfavorable attitude towards organ donation in medical students of a university in Lambayeque - Gonzáles-Chachapoyas, Lizeth (2020)
Introduction: In our country, organ donation has one of the lowest rates worldwide, many factors intervene so that this index can be increased, since there is a high demand for patients who require altruistic attitude both for potential donors and for their families. Objective: to determine the factors associated with an unfavorable attitude towards organ donation in students of the medical faculty of the Catholic University of Santo Toribio de Mogrovejo in 2015. Material and methods: cross-sectional analytical observational study executed in 377 students of the USAT faculty of medicine, to whom a validated data collection instrument was applied to measure the unfavorable attitude towards organ donation, with a 0.77 reliability according to Crombach's alpha and 0.5 validity according to the KMO test Results: Only 138 students (36.6%) said they agreed with organ donation and had a favorable attitude while 239 (63.4%) found an unfavorable attitude, only 89 participants (23.6%) mentioned agree that only people who are close to death should donate organs and 323 (85.6%) stated that the quality of life of the best people I would pray to receive an organ Conclusions: A high frequency of unfavorable attitude towards organ donation was estimated in students of the Faculty of Medicine at a University of Lambayeque in 2015.